Invasion in patchy landscapes is affected by dispersal mortality and mate‐finding failure. Issue 12 (2nd December 2016) - Walter, Jonathan A.; Firebaugh, Ariel L.; Tobin, Patrick C.; Haynes, Kyle J.
Abstract: Range expansions are a function of population growth and dispersal, and nascent populations often must overcome demographic Allee effects (positive density dependence at low population densities) driven by factors such as mate‐finding failure. Given the importance of individual movement to mate finding, links between landscape structure and movement may be critical to range expansion; however, landscape effects on other factors including mortality may be equally or more important. In one of the most comprehensive investigations of the interactions of these processes to date, we combined field experiments, simulation modeling, and analysis of empirical spread patterns to investigate how landscape structure affected the spread of the gypsy moth in Virginia and West Virginia. In experiments designed to assess how landscape attributes affect mate finding, we found adult males resisted leaving forest patches and the probability of locating a pheromone source declined more rapidly over distance in non‐forest matrix than in forest. We used these findings to develop individual‐based simulation models of gypsy moth population dynamics and spread in complex patch‐matrix landscapes. The models produced an Allee effect that strengthened with reductions in forested area, but owing more so to dispersal mortality than to effects on mate location. Predicted maximum rates of population spread grew with increases in forest area due to increasing success of long‐distance transport events. Evaluations of empirical data showed relationships between spread rates and landscape structure largely consistent with model predictions. We conclude rates of spread were largely driven by long‐distance dispersal events, the success of which was influenced primarily by dispersal mortality of larvae in unsuitable matrix, and that landscape effects on mate location played a secondary role. Though influences of landscape structure on mate location appear to be unimportant to the spread of the gypsy moth, we predict they would have stronger effects on more dispersive species.